Attitudes and behaviours of adolescents towards antibiotics and self-care for respiratory tract infections: a qualitative study. Issue 5 (6th June 2017) - Hawking, Meredith KD; Lecky, Donna M; Touboul Lundgren, Pia; Aldigs, Eman; Abdulmajed, Hind; Ioannidou, Eleni; Paraskeva-Hadjichambi, Demetra; Khouri, Pauline; Gal, Micaela; Hadjichambis, Andreas Ch.; Mappouras, Demetrios; McNulty, Cliodna AM
Abstract : Background: To understand attitudes and behaviours of adolescents towards antibiotics, antimicrobial resistance and respiratory tract infections. Design: Qualitative approach informed by the Theory of Planned Behaviour. Semi-structured interviews and focus groups were undertaken. We aimed to inform the development of an intervention in an international setting to improve antibiotic use among adolescents; therefore on completion of thematic analysis, findings were triangulated with qualitative data from similar studies in France, Saudi Arabia and Cyprus to elucidate differences in the behaviour change model and adaptation to diverse contexts. Setting: 7 educational establishments from the south of England. Participants: 53 adolescents (16–18 years) participated in seven focus groups and 21 participated in interviews. Results: Most participants had taken antibiotics and likened them to other common medications such as painkillers; they reported that their peers treat antibiotics like a 'cure-all' and that they themselves were not interested in antibiotics as a discussion topic. They demonstrated low knowledge of the difference between viral and bacterial infections.Participants self-cared for colds and flu but believed antibiotics are required to treat other RTIs such as tonsillitis, which they perceived as more 'serious'. Past history of taking antibiotics for RTIs instilled the belief that antibiotics were required for future RTIs. Those who characterised themselves as 'non-science students' were less informed about antibiotics and AMR. Most participants felt that AMR was irrelevant to them and their peers. Some 'non-science' students thought resistance was a property of the body, rather than bacteria. Conclusion: Addressing adolescents' misperceptions about antibiotics and the treatment of RTIs using a behaviour change intervention should help improve antibiotic awareness and may break the cycle of patient demand for antibiotics to treat RTIs amongst this group. Schools should consider educating all students in further education about antibiotic usage and AMR, not only those taking science.